2012 IEEE Conference on Computational Intelligence for Financial Engineering &Amp; Economics (CIFEr) 2012
DOI: 10.1109/cifer.2012.6327793
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of feed-forward and recurrent neural networks in time series forecasting

Abstract: Abstract-Forecasting performances of feed-forward and recurrent neural networks (NN) trained with different learning algorithms are analyzed and compared using the MackeyGlass nonlinear chaotic time series. This system is a known benchmark test whose elements are hard to predict. Multilayer Perceptron NN was chosen as a feed-forward neural network because it is still the most commonly used network in financial forecasting models. It is compared with the modified version of the so-called Dynamic Multi-layer Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 8 publications
0
26
0
Order By: Relevance
“…[33] compares the feedforward model with the radial basis neural network. [34] compares the feedforward model with the recurrent neural network. This is not sufficient to recognize ….…”
Section: Introductionmentioning
confidence: 99%
“…[33] compares the feedforward model with the radial basis neural network. [34] compares the feedforward model with the recurrent neural network. This is not sufficient to recognize ….…”
Section: Introductionmentioning
confidence: 99%
“…Thus, previous input and output values may be used for current output calculation. Analysis of several independent papers [15][16][17] showed that amongst various architectures of networks such as focused time delay, distributed time delays, Jordan, Elman, Hopfield, Hamming, the most suitable architecture for time-serious processing is non-linear autoregressive model with exogenous inputs (NARX). Basically it is multilayer perceptron with shortterm memory.…”
Section: Methodsmentioning
confidence: 99%
“…An NN method is applied in this study for predicting the soil moisture dynamics because of their ability to produce robust functions approximating complex processes [ 45 ]. However, traditional feedforward neural networks (FFNNs) have limited ability to model dynamic data because they are unable to preserve previous information, resulting in suboptimal predictions when they are applied in modelling highly causal systems [ 46 ]. The learning capability of FFNNs can be improved through additional pre-processing of dynamic data and combining the FFNN with other methods including genetic algorithms [ 47 ] and fuzzy logic [ 36 ].…”
Section: Introductionmentioning
confidence: 99%